METODE LANGSUNG DALAM PEMBELAJARAN BAHASA ARAB DI PONDOK PESANTREN AL MUAYYAD SURAKARTA - Azizah, Ana Sofiyatul (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2022)
One method of learning Arabic in Al Muayyad Islamic Boarding School Surakarta is the use of the direct method. This method emphasizes the practice of continuous conversation between teachers and students using Arabic without the slightest use of the mother tongue, both in explaining the meaning of vocabulary and translating. The purpose of the direct method here is to train the students to be able to communicate in Arabic. Arabic learning at the Al Muayyad Islamic Boarding School in Surakarta is implemented through muhadatsah learning/conversation practice (learning to talk/practicing dialogue), muthola'ah (learning to read), imla'/dictation (learning Arabic by dictating), and qowaid (nahwu shorof learning). The learning of muhadatsah, muthola'ah, and imla' is applied using the direct method while qowaid (learning nahwu shorof, namely learning about Arabic grammar) is carried out by the inductive method. Keywords: direct method, learning, Arabic